Three-year prospective study on olfaction of patients with Parkinson's disease. Issue 5 (October 2020) - Fujio, Hisami; Inokuchi, Go; Kuroki, Shunsuke; Tatehara, Shun; Katsunuma, Sayaka; Kowa, Hisamoto; Nibu, Ken-ichi
Abstract: Objective: We conducted a 3-year prospective study on olfaction of patients with Parkinson's disease (PD) in order to examine the severity and frequency of smell disorder in PD using odor identification test, Open Essence (OE) and to verify the validity of olfactory tests as a predictor of cognitive symptom onset of PD. Patients and methods: We conducted a prospective study by performing an annual examination over a 3-year period. For 56 cases diagnosed with PD by the Department of Neurology at our hospital, OE and Jet Stream Olfactometry (JSO) were performed to assess the olfactory function, and Mini-Mental-State Examination (MMSE) was conducted to measure cognitive impairment. Results: At the beginning, 56 cases were examined, of which 42 remained to be followed up for 3 years. Based on the results of baseline, we found a correlation between OE and the average cognitive thresholds of JSO, but did not find any correlation between OE and MMSE. OE (median 4.0 → 4.0) and the average cognitive thresholds of JSO (median 2.2 → 1.6)　decreased after 3 years, and MMSE (median 29 → 29) also declined, but not significantly. At the 3rd year, 6 cases with MMSE score of 23 or less were identified as suspected dementia and 36 cases with more than 24 points were defined as an invariant group. In order to distinguish these two groups, OE scores of baselines were evaluated with a combination of 12 odors. Sensitivity 1.0 and specificity 0.722 were obtained and the sensitivity + specificity value (1.722) was the highest when the number of correct answers was 4 or less using an odor combination of lumber, menthol, Japanese orange, gas for household use, Hinoki cypress and condensed milk. Conclusion: When the number of correct answers of 6 odors (lumber, menthol, Japanese orange, gas for household use, Hinoki cypress and condensed milk) is 4 or less in patients with PD, there is a possibility that MMSE declines in 3 years.